2023
DOI: 10.3390/genes14112102
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Causalities of Environmental and Genetic Factors for Differential Somatic Cell Count and Mastitis Pathogens in Dairy Cows Using Structural Equation Modelling

Patricia Wagner,
Kerstin Brügemann,
Tong Yin
et al.

Abstract: The aim of this study was to establish and evaluate a structural equation model to infer causal relationships among environmental and genetic factors on udder health. For this purpose, 537 Holstein Friesian cows were genotyped, and milk samples were analyzed for novel traits including differential somatic cell counts and specific mastitis pathogens. In the structural model, four latent variables (intramammary infection (IMI), production, time and genetics) were defined, which were explained using manifest meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Conjoint analysis revealed that the 12 shared DEPs were involved in ion homeostasis and absorption. Previous studies have shown that DEPs, such as SLC34A2 [30,31], PRKCB [32], FTH1 [1], and MAPK1 [33], could be putative biomarkers for mastitis. The PPI network displayed 12 candidate DEPs interacting with all selected GO terms, pathways, and DEPs, especially SLC34A2, indicating that these DEPs participate in the regulation of Ca/P metabolism and homeostasis via different routes.…”
Section: Discussionmentioning
confidence: 99%
“…Conjoint analysis revealed that the 12 shared DEPs were involved in ion homeostasis and absorption. Previous studies have shown that DEPs, such as SLC34A2 [30,31], PRKCB [32], FTH1 [1], and MAPK1 [33], could be putative biomarkers for mastitis. The PPI network displayed 12 candidate DEPs interacting with all selected GO terms, pathways, and DEPs, especially SLC34A2, indicating that these DEPs participate in the regulation of Ca/P metabolism and homeostasis via different routes.…”
Section: Discussionmentioning
confidence: 99%